2019
DOI: 10.1097/md.0000000000018468
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new genes of pleomorphic adenoma

Abstract: Pleomorphic adenoma is the most common salivary gland neoplasm with a variety of histologic appearances. Due to this diversity, precise preoperative diagnosis through fine needle aspiration cytology is difficult. This study sought to identify the differentially expressed genes in pleomorphic adenoma to aid precise diagnosis and clarify the mechanism of tumorigenesis. Suppressive subtractive hybridization was performed on pleomorphic adenoma tissues and the corresponding normal salivary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…The results of the Kaplan-Meier plotter analysis determined that the high expression groups of CD44, CCND3, NCALD and MACF1 had an improved prognosis compared with the low expression groups, while KCTD15 exhibited the opposite trend. To the best of our knowledge, KCTD15 upregulation has never been reported to be associated with pathological states, although it has been indirectly associated with several types of cancer, such as pleomorphic adenoma and medulloblastoma (39,40). The specific role of KCTD15 in LUAD should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…The results of the Kaplan-Meier plotter analysis determined that the high expression groups of CD44, CCND3, NCALD and MACF1 had an improved prognosis compared with the low expression groups, while KCTD15 exhibited the opposite trend. To the best of our knowledge, KCTD15 upregulation has never been reported to be associated with pathological states, although it has been indirectly associated with several types of cancer, such as pleomorphic adenoma and medulloblastoma (39,40). The specific role of KCTD15 in LUAD should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 95%
“…The PA Gene 1, PLAG1, is reportedly activated by chromosome rearrangements in both pleomorphic adenoma and myoepithelioma [13,14]. Using a variety of cytogenetic, molecular cytogenetic and molecular karyotyping based techniques, Thielker et al [15] recently reported chromosomal and/or submicroscopic alterations in 5 of 14 cases of PA, e.g., jumping translocation, gene copy variations involving twist-replated protein 1 (TWIST1) and distal-less homeobox 5 (DLX5) genes [15] ) could be potential biomarkers for a precise diagnosis of PA [16]. Lastly, Mariano et al [17] report that PA exhibited only a few copy alterations with the most frequent involving chromosomes 8:8p21.3-p12 (gain), 8q12.1 (loss), 8p23.3-q24.3 (gain), and 8q12.1-q21.11 (gain).…”
Section: Clinical Presentation and Etiologymentioning
confidence: 99%
“…However, it is known that in more than 70% of the cases there is an association with abnormal karyotypes, involving a locus of the PLAG1 gene (Pleomorphic adenoma gene 1). Recently, new genes that may be involved in tumor formation have been identified 16 . In addition, there is evidence that exposure to UV (ultraviolet) rays increases the risk of developing it 3 .…”
Section: Introductionmentioning
confidence: 99%